Philosophical Attitudes of Vladimír Mináč in the Context of the Philosophy of the History of the Slovak Nation - PERNÝ, Lukáš; ŽGRADA, Radoslav (GNOSI: An Interdisciplinary Journal of Human Theory and Praxis, 2023)
Vladimír Mináč is one of the most important Slovak writers, essayists, participants of the antifascist Slovak National Uprising (arrested and taken to Mauthausen concentration camp and later to Dachau), and cultural figures of the 20th century. Despite the fact that he is a relatively well-known figure in Slovakia, and also thanks to the fact that he was the long-term chairman of Slovak Matica, the oldest cultural institution, since his works have not been translated, in the international context he is an unknown author. Mináč also became famous for his literary treatment of the Slovak National Uprising and his historical-philosophical treatment of this historical event. The most significant influence of his philosophy was gained by the essay collection Dúchanie do pahrieb (eng. Blowing into the Embers), which in the 1960s opened a discussion about the plebeian nature of Slovak history (especially for a review of the revolutionary events in 1848 and the role of the Štúr’s group in Slovak history). The presented study analyses his philosophical concept for the first time in an international context. The aim of the study is to present to the world his basic philosophical ideas on the occasion of the 100th anniversary of his birth, for which several events have been organised in 2022. The text was created in collaboration between a philosopher and a historian.